A Toba-scale eruption in the Early Miocene: The Semilir eruption, East Java, Indonesia - Smyth, H.; Crowley, Q.; Hall, R.; Kinny, Peter; Hamilton, P.; Schmidt, D. (Elsevier BV, 2011)
The Indonesian archipelago is well-known for volcanic activity and has been the location of three catastrophic eruptions in the last million years: Krakatau, Tambora and Toba. However, there are no reports of large magnitude eruptions during the earlier Cenozoic despite a long volcanic record in Indonesia during subduction of Indian Ocean lithosphere since the Eocene. Here we report an Early Miocene major eruption, the Semilir eruption, in south Java, the main phase of which occurred at 20.7 ± 0.02 Ma. This major volcanic eruption appears similar in scale, but not in type, to the 74 ka Toba event. Its products can be identified elsewhere in Java and are likely to have been distributed widely in SE Asia and adjacent oceans. The Semilir eruption could have triggered a climate response, but cannot yet be linked with certainty to Early Miocene climatic events such as glaciations.